TINJAUAN KESULITAN GURU BIOLOGI KELAS XI DALAM MELAKSANAKAN PENILAIAN BERBASIS KELAS DI SMA NEGERI SE KOTA PADANG - Junita, Elva; Risdawati, M.Si., Renny; Maizeli, Annika (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The assessment based on the class orienting to competence that want to attain in learning activity in the class. A variety of various assessment based on the class, such as: written test (paper and pencil test), giving assignment, performance assessment, project assessment, product assessment, attitude (affective), and Â the collection of assignment of the students (portfolio). The teacher still gets trouble in doing assessment based on the class. Thatâs because of decrease information that teacher gets. The goal of this assessment is to know about level difficulty and what are troubles that biology teacher class XI SMA at Padang faced in implementation assessment based on the class. A kind of this research is descriptive. Population and sample in this research is 23 biology teacher XI who spread 16 schools from all of SMA at Padang in 2014. This research doing by questionnaire test of difficulty biology teacher in implementation of assessment based on the class by validator that obtained is valid criteria. The result of assessment is the implementation of assessment based on the class percentage that showed by biology teacher class XI SMA at Padang about 82, 50% with less difficult category, so difficulty percentage of teacher just 17,5%. In all of assessment, only written test which categorized not difficult.